2020
DOI: 10.1111/jch.13895
|View full text |Cite
|
Sign up to set email alerts
|

Validity of anthropometric indices in predicting high blood pressure risk factors in Iranian children and adolescents: CASPIAN‐V study

Abstract: Anthropometric indices have been used as indicators for predicting hypertension (HTN) in children and adolescents but it is not clear which anthropometric measures are a better index for identifying elevated blood pressure (EBP) risk factors in pediatric population. Body mass index (BMI), waist circumference (WC), weight‐height ratio (WHR), a body shape index (ABSI) and blood pressure were measured in 14 008 children and adolescents aged 7‐18 years in a national school‐aged survey CASPIN V. Hypertension (HTN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Forty-one cross-sectional studies were included in the present study, including 138,561 children and adolescents (50% girls) aged between 3 and 19 years. The studies were conducted in the following countries: 11 studies were conducted in countries from the European region (Denmark, Estonia, Portugal, Spain, Scotland, Wales, Finland, Sweden, UK, Greece, Italy, Hungary, Belgium, France, Germany, and Austria) [20][21][22][23][24][25][26][27][28][29][30] ; 10 studies were conducted in countries from the Latin American region (Chile, Brazil, Mexico, and Venezuela) [31][32][33][34][35][36][37][38][39][40] ; 11 studies were conducted in East and Southeast Asian countries (Malaysia, South Korea, China, Taiwan, and Vietnam) [41][42][43][44][45][46][47][48][49][50][51] ; 3 studies were conducted in the USA [52][53][54] ; 1 study was conducted in Algeria 55 ; 1 study was conducted in India 56 ; 1 study was conducted in Iran 57 ; and 3 studies were conducted in South Africa. [58][59][60] Sample sizes ranged from 152 35 to 32,036 49 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one cross-sectional studies were included in the present study, including 138,561 children and adolescents (50% girls) aged between 3 and 19 years. The studies were conducted in the following countries: 11 studies were conducted in countries from the European region (Denmark, Estonia, Portugal, Spain, Scotland, Wales, Finland, Sweden, UK, Greece, Italy, Hungary, Belgium, France, Germany, and Austria) [20][21][22][23][24][25][26][27][28][29][30] ; 10 studies were conducted in countries from the Latin American region (Chile, Brazil, Mexico, and Venezuela) [31][32][33][34][35][36][37][38][39][40] ; 11 studies were conducted in East and Southeast Asian countries (Malaysia, South Korea, China, Taiwan, and Vietnam) [41][42][43][44][45][46][47][48][49][50][51] ; 3 studies were conducted in the USA [52][53][54] ; 1 study was conducted in Algeria 55 ; 1 study was conducted in India 56 ; 1 study was conducted in Iran 57 ; and 3 studies were conducted in South Africa. [58][59][60] Sample sizes ranged from 152 35 to 32,036 49 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[58][59][60] Sample sizes ranged from 152 35 to 32,036 49 participants. WHtR cutoffs ranged between 0.41 20 and 0.59 35 as follows: 10 studies reported cutoffs of 0.41 to 0.45 20,22,[24][25][26]32,42,48,58,60 ; 23 studies reported cutoffs of 0.46 to 0.50 [23][24][25][26][27][28][29][30][32][33][34]36,[43][44][45][46][47]51,[53][54][55]57,59 ; and 12 studies reported cutoffs ≥0.51. 21,30,31,33,35,[37][38][39]48,52,54,...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Many anthropometric indices are used to define obesity-associated hypertension. These include the most commonly used body mass index (BMI), waist circumference (WC), weight-to-hip ratio (WHR), and weight-to-height ratio (WHtR) [ 13 ]. Nonetheless, research shows that the predictive powers of anthropometric measures for hypertension are countries and ethnicities dependent [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 . Initially, 9642 articles were identified from the PubMed, Web of Science, and Cochrane databases, 26 studies were excluded after browsed the full-text, and 21 original articles were included for the meta-analysis in the end [ 6 , 22 – 41 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%